Correction of Acoustics in Historic Opera Theatres with the Use of Schroeder Diffuser - Tadeusz KAMISIŃSKI (Archives of Acoustics, 2013)
The paper deals with the problem of acoustic correction in historic opera theatres with the auditorium layout in the form of a horseshoe with deep underbalcony cavities limited with a semicircular wall surface. Both geometry of the cavities and excessive sound absorption determine acoustic phenomena registered in this area of the hall. The problem has been observed in the Theatre of Opera and Ballet in Lviv, Ukraine, where acoustic tests were carried out, simulation calculations performed, and finally a diffusion panel worked out designed for the rear wall of the underbalcony space. Acoustic measurements carried out after installation of the diffusers revealed favourable changes in the sound strength factor G within the range of medium and high frequencies in the underbalcony and auditorium centre area. By replacing textile tapestry with diffusion panels, a significant reduction of sound absorption was achieved for the frequency range above 1 kHz and an increase of uniformity of acoustic parameters registered in the hall. The method presented in the paper can be applied in historic halls of the similar type as well as contemporary rooms where there is a need for correction of acoustic flaws related to sound focusing or the echo effect.